Time domain approach to identify system properties in coupled structures - Mehfuz, Nagib (My University, 2016)
In this thesis, coupled structures which consist of two beams that are coupled with a spring between them has been studied. Free mobilities are identified as system properties of the coupled structure. The first approach was a virtual study comparing the free mobilities from the simulation and using the time domain approach. LMS algorithm is used to solve the equations in the time domain. Next step is to use the same method and apply in different degrees of freedom (one degree, two degrees) to calculate the error between the two methods. Lastly, the effect of some of the parameters like spring constant, isotropic loss factor, and damping coefficient are observed .The results in first two cases suggested that in one degree and two degrees the free mobilities of the sending and receiving points can be recreated almost accurately. And among other parameters, the spring constant and isotropic loss factor have the most effect on the results.
Keywords: Building Futures; Akustik; Building Futures; Acoustics